Genome-Wide Analysis of Differentially Expressed miRNA in PLX4720-resistant and Parental Human Thyroid Cancer Cell Lines - Varmeh, Shohreh (Surgery, 2015)
BACKGROUND: Investigating BRAF((V600E)) inhibitors (BRAFi) as a strategy to treat patients with aggressive thyroid tumors harboring BRAF((V600E)) mutant is currently in progress and drug resistance is expected to pose a challenge. MicroRNAs are involved in development of resistance to a variety of drugs in different malignancies. METHODS: miRNA expression profiles in the human anaplastic thyroid cancer cell line (8505c) were compared to its PLX4720-resistant counterpart (8505c-R) using Illumina deep sequencing. We conducted a functional annotation and pathway analysis of the putative and experimentally validated target genes of the significantly altered miRNAs. RESULTS: We identified 61 known and 2 novel miRNAs whose expression was significantly altered in 8505c-R. qRT-PCR validated altered expression of 7 selected miRNAs in 8505c-R and BCPAP-R (PLX4720-resistant papillary thyroid cancer cell line). We found 14 and 25 miRNAs whose expression levels changed significantly in 8505c and 8505c-R, respectively, following treatment with BRAFi. MAPK and PI3K-AKT pathways were among the prominent targets of many of the deregulated miRNAs. DISCUSSION: We have identified a number of miRNAs that could be used as biomarkers of resistance to BRAFi in patients with thyroid cancer. In addition, these miRNAs can be explored as potential therapeutic targets in combination with BRAFi to overcome resistance.